OIV and NeVI EUV line ratios in the sun - Dwivedi B.N.; Gupta A.K. (My University, 2025)
Steady state level population of the first 11 levels of boron-like ions-OIV and NeVI- have been computed as a function of electron density and temperature. The collisional and spontaneous radiative processes have been taken into account. Photo-excitation between the two levels of the ground term has also been considered. Using the computed level populations, line intensity ratios have been computed as a function of electron density and temperature. Density measurement from these diagnostic line intensity ratios has been discussed using observational data available from rockets and satellites. Theoretical line intensities from these ions have also been computed and compared with available observational data. © 1991.